Facile measurement of surface heat loss from polymer thin films via fluorescence thermometry. Issue 8 (27th December 2017) - Firestone, Gabriel; Bochinski, Jason R.; Meth, Jeffrey S.; Clarke, Laura I.
ABSTRACT: Quantitative determination of heat loss and transport within complex systems having inhomogeneous temperatures and several different components is important for applications ranging from electronics to solar cells. An approach and material system to study heat transport within and heat loss from polymer thin films is presented. In a thin film configuration with a cylindrical heating source, the theoretical solution for temperature as a function of radial position can be determined from fundamental principles. Use of embedded fluorescent molecules as temperature probes and manipulation of the relative location of heating and thermometry light sources allows experimental measurements of temperature versus position within the plane of the film. For a large range of practical cases, the exact theoretical solution can be well‐approximated by a single term, which enables a fit to experimental data, and subsequent determination of either the heat loss coefficient at the film's surface or the material's effective thermal conductivity. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 643–651 Abstract : In applications ranging from electronics to solar cells, heat is generated and moves through complex systems with multiple components and inhomogeneous temperatures. In this work, a combination of theoretical and experimental approaches is presented that could enable triage of multi‐component polymeric materials proposed for effective heat dissipation. In particular, heat loss from a thin film surface is measured and the associated heat transport within the film is discussed.